Motor Responses of Lumbar Erector Spinae Induced by Electrical Vestibular Stimulation in Seated Participants - Desgagnés, Amélie; Desmons, Mikaël; Cyr, Jean-Philippe; Simoneau, Martin; Massé-Alarie, Hugo (Frontiers in Human Neuroscience, 2021)
Introduction: The study of motor responses induced by electrical vestibular stimulation (EVS) may help clarify the role of the vestibular system in postural control. Although back muscles have an important role in postural control, their EVS-induced motor responses were rarely studied. Moreover, etthe effects of EVS parameters, head position and vision on EVS-induced back muscles responses remain little explored. Objectives: To explore the effects of EVS parameters, head position, and vision on lumbar erector spinae muscles EVS-induced responses. Design: Exploratory, cross-soectional study Materials and methods: Ten healthy participants were recruited. Three head positions (right, left and no head rotation), 4 intensities (2, 3, 4, 5 mA) and 4 EVS durations (5, 20, 100, 200 ms) were tested in sitting position with eyes open or closed. EVS usually induced a body sway toward the anode (placed on the right mastoid). EMG activity of the right lumbar erector spinae was recorded. Variables of interest were amplitude, occurrence, and latency of the EVS-induced modulation of the EMG activity. Results: The short-latency response was inhibitory and the medium-latency response was excitatory. Increased EVS current intensity augmented the occurrence and the amplitude of the short- and medium-latency responses (more inhibition and more excitation, respectively). EVS duration influenced the medium-latency response differently depending on the position of the head. Right head rotation produced larger responses amplitude and occurrence than left head rotation. Opposite head rotation (left vs. right) did not induce a reversal of the short- and medium-latency responses (i.e., the inhibition did not become an excitation), as typically reported in lower legs muscles. The eyes open condition did not modulate muscle responses. Conclusions: Modulation of EVS parameters (current intensity and duration of EVS) affects the amplitude and occurrence of the lumbar erector spinae responses. In contrast, vision did not influence the responses, suggesting its minimal contribution to vestibulomotor control in sitting. The lack of response reversal in sagittal plane may reflect the biomechanical role of lumbar erector spinae to fine-tune the lumbar lordosis during the induced body sway instead. This hypothesis remains to be further tested.